211k views
16 votes
Simplify the following expression:

4x - 5.2y + 6y + 7.0x - 8x
Pleas i really need help this is confusing

User Dsissitka
by
5.5k points

2 Answers

13 votes

Answer:

3x+0.8y

Explanation:

4x-5.2y+6y+7x-8x

4x+7x-8x-5.2y+6y ( 4x+7x-8x → 3x)

3x-5.2y+6y ( -5.2y+6y → 0.8y)

3x+0.8y

Hope it helps! :)

User John Miner
by
5.8k points
10 votes

Answer: 3x +1.2y

Explanation:

you have to add the like terms together (the x’s plus the x’s, the y’s plus the y’s)

4x+7x=11x

11x-8x=3x

-5.2y+6y= 1.2y

Then you combine the x and the y for your answer.

3x+1.2y

User Mugentoki
by
5.4k points